Biokoagulan Sebagai Teknologi Koagulasi Untuk Pengendalian Kekeruhan Pada Pengolahan Air : Sebuah Tinjauan Sistematis - Fitrah, Muhammad Aidil; Kasim, Setiawan; Saleh, Muh.; Thohira, Morrin Choirunnisa (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Water pollution is a critical environmental challenge globally, particularly in Indonesia, which poses a significant threat to public health and natural ecosystems. To address this pressing issue, the application of efficient and environmentally friendly water treatment methods is essential; one promising approach is the utilization of biocoagulants as an alternative to chemical coagulants. This study aims to assess the effectiveness of biocoagulants in reducing water pollution in the form of turbidity, organic pollutants, and heavy metals in water. The research method used is a systematic literature review using a PRISMA diagram starting from secondary data collection, data presentation, and data processing from databases such as Google Scholar, Scopus, and Pubmed. Several studies showlants such as Moringa oleifera seeds, chitosan, and Opuntia ficus-indica have been proven effective in reducing water turbidity, organic pollutants, and heavy metals. Nonetheless, the application of biocoagulants still faces several challenges, such as variability in effectiveness depending on water type and local conditions and the need for more efficient production. Further research is needed to optimize the use of biocoagulants in large-scale water treatment. With the development of technology, biocoagulants have the potential to be a safer and environmentally friendly sustainable solution in water management, which is in line with global sustainability goals (SDGs 6).